Workspaces in Transition: Investigating Dwelling Adaptations for Young Professionals Working from Home - Ula, Zuhrotul Mawaddatil; Hayati, Arina; Cahyadini, Sarah (Sinektika: Jurnal Arsitektur, 2024)
Working from home (WFH) is becoming increasingly common. Technological developments and the COVID-19 pandemic have catalyzed the development of the concept of working from home. This has caused a shift in the meaning of housing from something separate from work to something that must accommodate work activities. A proper place to work in housing then becomes a necessity that cannot always be fulfilled. This research explores how housing accommodates work activities. The study is conducted on how participants negotiate space by using and changing the attributes of the dwelling to create an ideal work setting. Interviews and auto-photography were conducted with young professionals aged 20 to 25 who have experience working from home with varying frequency. The results show that work activities take place in a variety of residential settings. Participants chose their work setting based on the type of work activities performed as well as personal preferences. Some interconnected factors that influence the work setting in the residence are the type of work activity, privacy, attributes, and atmosphere. Participants also intervene in the dwelling by using existing spaces and attributes to form ideal working conditions that meet their needs.